Suplementação isolada e combinada de cafeína e maltodextrina: efeito agudo no desempenho de corredores - Kravchychyn, Ana Claudia Pelissari (2013)
Caffeine and maltodextrin are among the most consumed supplements in sports for competitive and health contexts, being used isolated or combined. However, few studies analyzed the effects of these supplementation in situations of evaluation to determine Peak running speed (Vpeak), Time limit (Tlim) and 10 km running performance that generate variables used for training prescribing and evaluation of the training effects. Thus, the aim of this study was to evaluate the acute effect of isolated and combined supplementation of caffeine (CAF) and maltodextrin (MALT) in physiological and performance variables of runners. Participated in the study 15 male runners ( 25.2 ± 2.8 years, 79.9 ± 7.7 kg, 180.0 ± 6.0 cm, Body Mass Index - BMI 24.6 ± 1.9 kg.m-2, body fat - %G 14.2 ± 2.9% and resting metabolic rate -TMR 2185.7 ± 232.9 kcal-day-1) with background in 10 km running performance (time between 38 and 60 min). Participants performed all tests in four supplementation conditions: placebo + placebo (PLA + PLA), placebo + caffeine (CAF + PLA), maltodextrin + placebo (PLA + MALT), and maltodextrin + caffeine (CAF + MALT). CAF was administrated by capsules (5 mg.kg-1) taken 60 minutes before the tests, and 30 minutes before the tests participants ingested MALT (1 g.kg-1). The PLA effect was achieved for CAF by identical empty capsules, and for the MALT by Clight juice® (0g carbohydrates). Participants performed four incremental tests preceded by a three minutes warming at 6 km.h-1 and started the protocol at 8 km.h-1 with increments of 1 km.h-1 every three minutes for the determination of Vpeak; four constant load tests in order to determine the Tlim at 100% of PLA + PLA Vpeak; and four 10 km running performances. All tests were conducted under the four supplementation conditions. At the end of each test it was evaluated the maximum perceived exertion (RPEmax) and maximum heart rate (HRmax). Blood samples from the earlobe were collected at the beginning of the tests, at the end, and at the 3º, 5º, and 7º minutes after the end of each laboratory and 10 km performance tests, to determine the lactate peak concentration (LApeak) and blood glucose. The variables obtained in each supplementation condition were compared by the Anova for repeated measures followed by the Bonferroni post hoc. The sphericity assumption was verified by the Mauchly test and when violated, the degrees of freedom were corrected using estimated sphericity by the Greenhouse-Geisser test. Relations between Vpeak and performance were demonstrated by Pearson's correlation coefficient (r), coefficient of determination (R2), and standard error of estimate (SEE). A significance level of P < 0.05 was adopted for all analyzes. The effect size (ES) and the minimal detectable change (MDC) were calculated only for the performance variables. The main results showed that isolated and combined acute supplementation of caffeine and maltodextrin did not altered the Vpeak and their respective Tlim, and the 10 km running performance Vmean. Furthermore, moderate and high correlations were found between Vpeak and the x 10 km running performance under the same supplementation conditions. The isolated and combined supplementation of caffeine and maltodextrin did not altered values of RPEmax and glucose concentrations after exercise (GLpost) in the Vpeak test; values of HRmax, RPEmax, lactate concentrations before and after (LApre, LApost), and GLpost in the Tlim tests; and also, values of HRmax, concentrations of LApre, LApost and GLpost in the 10 km performances. Higher values of HRmax were obtained in the CAF+MALT condition compared to PLA+PLA; and the conditions PLA+CAF and CAF+MALT presented higher values of LApeak compared to PLA+MALT in the Vpeak test. In conclusion, isolated and combined supplementation of CAF and MALT does not alter performance variables such as Vpeak and their respective Tlim, and the 10 km running performance Vmean. Moreover, when used together, these supplements appear to influence the HRmax, and CAF or CAF+MALT seems to influence LApeak concentrations.